2018
DOI: 10.1111/ctr.13158
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of frailty compared to peak oxygen consumption and B‐type natriuretic peptide in patients with advanced heart failure

Abstract: Frailty assessment has become an integral part of the evaluation of potential candidates for heart transplantation and ventricular assist device (HTx/VAD). The impact of frailty, as a heart failure risk factor or to identify those who will derive the greatest benefit with HTx/VAD remains unclear. The aim of this study was to evaluate the independent prognostic relevance of frailty assessment from peak oxygen consumption (peak VO ) or B-type natriuretic peptide (BNP) on mortality in patients referred for advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Moayedi et al showed that, adjusted for B-type natriuretic peptide or peak oxygen consumption (VO 2 ), frailty identified using the phenotype of frailty was not associated with increased mortality in people with advanced HF. [80] However, Moayedi et al also found that when peak VO 2 was stratified into two categories (≥12 ml/kg/min versus <12 ml/kg/min), frailty was associated with a 72% higher risk of death in this group. [80] Of the individual phenotype of frailty components, low physical activity assessed with the Duke Activity Status Index was associated with the highest risk of death.…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moayedi et al showed that, adjusted for B-type natriuretic peptide or peak oxygen consumption (VO 2 ), frailty identified using the phenotype of frailty was not associated with increased mortality in people with advanced HF. [80] However, Moayedi et al also found that when peak VO 2 was stratified into two categories (≥12 ml/kg/min versus <12 ml/kg/min), frailty was associated with a 72% higher risk of death in this group. [80] Of the individual phenotype of frailty components, low physical activity assessed with the Duke Activity Status Index was associated with the highest risk of death.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…[80] However, Moayedi et al also found that when peak VO 2 was stratified into two categories (≥12 ml/kg/min versus <12 ml/kg/min), frailty was associated with a 72% higher risk of death in this group. [80] Of the individual phenotype of frailty components, low physical activity assessed with the Duke Activity Status Index was associated with the highest risk of death. [81,82] A study by Martin-Sánchez et al showed that the presence of physical frailty in people with moderate disability has an impact on 30–day mortality in people ≥65 years with acute decompensated HF attending an emergency department.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…16 In heart transplant recipients, those who developed deep-sternal wound infection post-transplant were more likely to be obese (46% and 17% obesity in patients with and without deep-sternal wound infection, respectively), 17 potentially increasing the risk of mortality due to infection. 23 Low BMI is likely a marker for an increased prevalence of frailty. 19 The ISHLT registry has shown that long-term survival postheart transplant is significantly lower in diabetic patients compared to those without diabetes (12% reduction in survival by 10-year post-transplant).…”
Section: Primary Findingsmentioning
confidence: 99%
“…22 Among the individual domains used to assess frailty, unintentional weight loss is a strong predictor of mortality in patients with advanced heart failure (HR 2.55, 95% CI 1.16-5.62). 23 A recent case series suggests 26% of patients undergoing advanced therapies for heart failure (heart transplant or ventricular assist device implantation), die within the index hospital admission or within 30-days post operation, all of whom were classified as frail or prefrail. 23 Low BMI is likely a marker for an increased prevalence of frailty.…”
Section: Primary Findingsmentioning
confidence: 99%
See 1 more Smart Citation